Model Bangkitan Perjalanan Masyarakat Penyintas di Kota Palu (Studi Kasus : Hunian Tetap Tondo 1) - R. Rahman; M. Mashuri; E.R. Labaso; H. Hildayanti (Civil Engineering Department, Tadulako University, 2023)
Tondo 1 permanent housing is intended for residents affected by the earthquake and tsunami on 28 September 2018. Furthermore, Tondo 1 permanent housing is now inhabited by people from various areas such as Petobo, Mamboro, Balaroa, Talise, and Tondo Villages. The rapid population growth in the tondo village after the relocation resulted in increased movements in the tondo village due to a large number of trips. This affects the trip generation of people who travel from their homes to the Central Business District (CBD) to carry out their daily activities. This study aims to determine the community's characteristics and model the trip generation in Tondo 1 permanent housing. This study used the multiple linear regression method. Based on the calculation, two variables affect the trip: the number of working family members (X2) and the number of vehicle ownership (X5). Therefore, the analysis model of the trip generation of survivors at Tondo 1 permanent housing area is obtained as follows: Y = 1.766 + 0.325 X2 + 0.271 X5.